A favourable outcome of a bilateral injury of the shoulder joints - Litvin, Yuriy; Gulay, Albert; Litvin, Valerіy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
By the frequency of their occurrence, shoulder dislocations take the first place among all dislocations and make from 34.8 % to 65.0 %. Depending upon the mechanism of injury development and direction of the effective force the head of humerus displaces to some side with a resultant outcome of the injury: shoulder dislocations and damages of soft tissue or even bone structures. Sometimes this problem complicates diagnosis and treatment. Particular difficulties in treatment are caused by neglected injuries. The authors describe an especially severe case with bilateral neglected dislocation of both shoulder joints. On examination, damages of the articular capsule, ligaments and tendons were diagnosed. A thoroughly planned surgical approach to reinsertion of the tendoligamentous apparatus of the shoulder joints, their temporary immobilization and subsequent rehabilitation resulted in a favourable outcome.